Intimin type influences the site of human intestinal mucosal colonisation by enterohaemorrhagic Escherichia coli O157:H7. Issue 2 (1st February 2002) - Fitzhenry, R J; Pickard, D J; Hartland, E L; Reece, S; Dougan, G; Phillips, A D; Frankel, G
Abstract : Background: Enterohaemorrhagic (EHEC) and enteropathogenic (EPEC) Escherichia coli epithelial cell adhesion is characterised by intimate attachment, and attaching and effacing (A/E) lesion formation. This event is mediated in part by intimin binding to another bacterial protein, Tir (translocated intimin receptor), which is exported by the bacteria and integrated into the host cell plasma membrane. Importantly, EPEC (O127:H6) and EHEC (O157:H7) express antigenically distinct intimin types known as intimin α and γ, respectively. EHEC (O157:H7) colonises human intestinal explants although adhesion is restricted to the follicle associated epithelium of Peyer's patches. This phenotype is also observed with EPEC O127:H6 engineered to express EHEC intimin γ. Aims: To investigate the influence of intimin on colonisation of human intestine by E coli O157:H7, and intimin types on tissue tropism in humans. Methods: Human intestinal in vitro organ culture with wild type and mutant strains of O157:H7 were employed. Results: Introducing a deletion mutation in the eae gene encoding intimin γ in EHEC (O157:H7) caused the strain (ICC170) to fail to colonise human intestinal explants. However, colonisation of Peyer's patches and A/E lesion formation were restored with intimin γ expression from a plasmid (ICC170 (pICC55)). In contrast, complementing the mutation with intimin α resulted in a strain (ICC170 (pCVD438)) capable of colonising and producing A/E lesions on both Peyer's patch and other small intestinal explants. Conclusion: Intimin is necessary for human intestinal mucosal colonisation by E coli O157:H7. Intimin type influences the site of colonisation in a Tir type independent mechanism; intimin γ appears to restrict colonisation to human follicle associated epithelium.